Clare Woods - as I please - Mullins, Charlotte 1972-; Leader, Darian; Bittencourt, Ela (Art/Books, 2024)
Clare Woods is one of the most idiosyncratic painters working in Britain today. Her highly colouristic paintings hover between abstraction and representation, expressing both a poetic romanticism and an unnerving psychic charge. Her unique and distinctive painting style is informed by her background in sculpture. She uses large, bold, and gestural brushstrokes of thick, fluid paint to make figurative paintings that are usually based on photographs of real objects, interiors, and people, but enlarged, cropped, and distorted almost to the point of illegibility. In this way, she conceptually empties the source photograph to replace it with a new interpretation. This physical breakdown of the image during the act of painting forces the viewer to question their ability to decipher what is in front of them. Much of Woods’ recent work is concerned with the fine line between mortality, fragility, sickness, and health, while at the same time creating a psychological space that is shared and inhabited by artist and viewer alike. This beautiful book follows Woods’ previous monograph Strange Meetings, published by Art / Books in 2016. It presents all of the artist’s most important paintings of the past decade, as well as the many prints and collages that have grown out of her painting practice in recent years. Critic and art historian Charlotte Mullins writes a lively and accessible introduction to the artist’s work and discusses some of its precedents and influences from art history, while psychoanalyst Darian Leader considers the psychological roots of her practice. Writer Ela Bittencourt completes the volume with a text that examines the push-and-pull between familiarity and alienation, knowability and ambiguity, that characterizes Woods’ alluring, seductive, and powerful works
Keywords: Woods, Clare -- 1972-; Bildband